Choroid plexus carcinoma of the third ventricle: A rare tumor presenting at an unusual site - Bansal, Manishi; Jindal, Anupam; Mohandass, P; Jindal, Ankush (Indian Journal of Case Reports, 2025)
We present an extremely rare case of choroid plexus carcinoma (CPC) of the third ventricle of the brain. An adult female presented with symptoms of raised intracranial pressure. On magnetic resonance imaging brain, a solid cystic mass was seen in the third ventricle along with obstructive hydrocephalus. Ventriculoperitoneal shunt was done initially to relieve hydrocephalus followed by complete tumor excision. Pathologically, it was confirmed as CPC. She was given adjuvant radiation to a dose of 58 Gy in 29 fractions by volumetric modulated arc therapy. After 1 year of follow-up, the patient is disease-free.